The Relationship of Knowledge, Parity and Anxiety With the Event of Severe Preeclamsia in Hospital General of Wood Area 2021 - Reni Aryanti; Siti Aisyah; Helni Anggraini (Institute of Computer Science (IOCS), 2022)
Preeclampsia is a health problem that requires special attention because preeclampsia is a high cause of maternal and perinatal mortality, especially in developing countries. Until now preeclampsia and eclampsia are still